V-pit to truncated pyramid transition in AlGaN-based heterostructures. (15th October 2015) - Mogilatenko, A; Enslin, J; Knauer, A; Mehnke, F; Bellmann, K; Wernicke, T; Weyers, M; Kneissl, M
Abstract: The formation of three-dimensional truncated pyramids after the deposition of AlN/GaN superlattices onto (0001) AlN/sapphire templates has been analysed by atomic force microscopy as well as transmission electron microscopy. V-pits in AlN layers and the formation of nano-mounds around the v-pit edges are suggested to be responsible for the pyramid formation. Keeping the individual AlN layer thickness at 2.5 nm in the 80xAlN/GaN superlattice, the transformation to the three-dimensional pyramids is observed when the individual GaN layer thickness exceeds 1.5 nm. A subsequent overgrowth of the pyramidal structures by AlGaN results in inhomogeneous Ga distribution in the layers and laterally inhomogeneous strain states. Nevertheless, compared to the growth on planar layers, the overgrowth of the truncated pyramids leads to a slight reduction in dislocation density from 1 · 10 10 cm −2 (for GaN thickness of 1 nm in SL) to 7 · 10 9 cm −2 (for GaN thickness of 2 nm in SL). The non-planar growth front and thus the compositional inhomogeneity in AlGaN vanish gradually with increasing AlGaN thickness. As a result, homogeneous 4 μ m thick Al0.5 Ga0.5 N buffer layers suitable for the fabrication of UV-B LED structures can be obtained.